WAYS TO INCREASE LABOR RESOURCES AND POTENTIAL IN THE SERVICE SECTOR IN THE CONDITIONS OF ECONOMIC MODERNIZATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article was devoted to the economics of the reformation in conditions associated with the restoration of conditions in accordance with the tasks of solving this problem, a competitive economy that provides